A clinical sign of adenocystic tumour of the trachea. Issue 4 (July 1973) - Singh, H. M.; Thomas, D. M. E.
Abstract : Singh, H. M., and Thomas, D. M. E. (1973) . Thorax, 28, 442-443. A clinical sign of adenocystic tumour of the trachea . Three patients with intrathoracic adenocystic tumour of the trachea presented as difficult diagnostic problems. All three patients had been labelled as psychiatric problems. Present in two of the cases, the sniff sign proved diagnostic and occurred at a stage when occlusion of the trachea during expiration was almost total. In order to breathe, the patients drew in small sharp, sniffing breaths. The sign owes its name to this pattern of breathing.